UPM, UNHAS enter into academic and research collaboration - Juferi, Noor Eszereen (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2023)
MAKASSAR, Jan 9 – University Putra Malaysia (UPM) has entered into an academic and research collaboration with Universitas Hasanuddin (UNHAS) through the exchange of a memorandum of understanding (MoU) here.